2012
DOI: 10.1103/physreva.85.022342
|View full text |Cite
|
Sign up to set email alerts
|

Symmetries and security of a quantum-public-key encryption based on single-qubit rotations

Abstract: Exploring the symmetries underlying a previously proposed encryption scheme which relies on single-qubit rotations, we derive an improved upper bound on the maximum information that an eavesdropper might extract from all the available copies of the public key. Subsequently, the robustness of the scheme is investigated in the context of attacks that address each public-key qubit independently. The attacks under consideration make use of projective measurements on single qubits and their efficiency is compared t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…(24). Both problems were raised by Gao et al in 2009 [58, 59], and improved quantum public-key cryptography protocols were suggested [58][59][60][61].…”
Section: Security Of Quantum Public-key Cryptographymentioning
confidence: 99%
“…(24). Both problems were raised by Gao et al in 2009 [58, 59], and improved quantum public-key cryptography protocols were suggested [58][59][60][61].…”
Section: Security Of Quantum Public-key Cryptographymentioning
confidence: 99%
“…Over a decade, the slowpacing of experimental realization [2], [3], [4] hampered the progress of QDS and other quantum protocols. Alternatively, we consider to construct a security model which can facilitate exploration of quantum one-way function to more scenarios and security analysis of related quantum cryptographic protocols, such as quantum digital signature schemes [5], [3], [6] and quantum public-key encryption schemes [7], [8].…”
Section: Motivationmentioning
confidence: 99%
“…Swati Sharma [7] implemented a quantum circuit for secret key distribution using quantum teleportation. In the recent paper V.Seyfarth [8] analysed the security of a quantum key encryption scheme based on single qubit rotations.…”
Section: Previous Workmentioning
confidence: 99%